An Environmental Scan of Adventure Therapy in Canada. (September 2016) - Ritchie, Stephen D.; Patrick, Krysten; Corbould, Gordon Marcus; Harper, Nevin J.; Oddson, Bruce E.
We report on an environmental scan (ES) of adventure therapy (AT) literature, organizations, and activities in Canada. The ES methodology involved (a) an examination of final reports related to a series of national symposiums on AT in Canada, (b) a review of academic literature related to AT in Canada, and (c) a summary of AT programs and courses offered at post-secondary institutions across Canada. Analysis of the reports from five AT symposiums revealed broad variability in terms of delegates and organizations represented and suggested that AT is practiced or endorsed by a diverse array of individuals and organizations across Canada. The literature review uncovered 113 relevant articles, book chapters, and papers with a substantial Canadian contribution. Canadian academic literature on the topic is sparse, and AT training and education opportunities at Canadian institutions are very limited. Implications for the future development of AT in Canada are shared.